2018
DOI: 10.1021/acsomega.8b02581
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted Removal of Tetracycline by a Fe/N–C Hybrids/H2O2 Fenton-like System

Abstract: In this work, the degradation of tetracycline (TC) in water by the integrated ultrasound (US)-Fenton process was investigated. For this, a new composite Fe/N–C- x ( x is the molar ratio of iron salt Fe(NO 3 ) 3 ·9H 2 O) catalyst was synthesized through simple carbonization of the mixture of glucose and iron salt Fe(NO 3 ) 3 ·9H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 53 publications
0
8
1
Order By: Relevance
“…on tetracycline (TC) ultrasound-assisted degradation using Fe/N–C- x hybrid/H 2 O 2 Fenton-like catalysts ( x stands for iron salt molar ratio (Fe(NO 3 ) 3 ·9H 2 O)). 136 Unlike previous reports, the removal of TC decreased from 93.8 to only 86.3 in 80 min by altering the pH from 3 to 11, indicating that this catalyst has high removal efficiencies in a wide pH range ( Fig. 20a ).…”
Section: Application Of Micro and Nanoscale Magnetic Catalytic System...contrasting
confidence: 59%
“…on tetracycline (TC) ultrasound-assisted degradation using Fe/N–C- x hybrid/H 2 O 2 Fenton-like catalysts ( x stands for iron salt molar ratio (Fe(NO 3 ) 3 ·9H 2 O)). 136 Unlike previous reports, the removal of TC decreased from 93.8 to only 86.3 in 80 min by altering the pH from 3 to 11, indicating that this catalyst has high removal efficiencies in a wide pH range ( Fig. 20a ).…”
Section: Application Of Micro and Nanoscale Magnetic Catalytic System...contrasting
confidence: 59%
“…Tetracycline hydrochloride is amphoteric compound with multiple ionizable functional groups. When pH is below 3.30, TC-HCl primary exists in the form of cation, zwitterion as main form when pH value is between 3.30 and 7.68, while forming the anion when pH is above 7.68 ( Yang et al, 2018 ; Sun et al, 2021 ). In this study, the removal efficiency of TC-HCl was investigated under various systems, catalyst dosage, H 2 O 2 concentration and pH value.…”
Section: Resultsmentioning
confidence: 99%
“…The fact suggested that there was interfacial interaction between CuS and Cu-CDs. 50 Compared with the freshly synthesized composites, the binding energies of Cu 2p 3/2 and Cu 2p 1/2 for the used catalyst shied to higher positions (935.3.0 and 956.0 eV), indicating the increasing amount of Cu 2+ aer the Fenton-like reaction. Two satellite peaks of Cu 2p 3/2 and Cu 2p 1/2 were enhanced, further conrming the increased quantities of Cu 2+ in the sample.…”
mentioning
confidence: 87%